Nationalism in Central Asia : a biography of the Uzbekistan-Kyrgyzstan border - Megoran, Nick (Central Eurasia in context., 2017)
"Nick Megoran explores the process of building independent nation-states in post-Soviet Central Asia through the lens of the boundary between Uzbekistan and Kyrgyzstan, using a combination of political, historical, ethnographic, and geographic frames to shed new light on this process."--Provided by publisher